2015
DOI: 10.1002/anie.201500695
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Hydrophobic–Hydrophilic Transition of Ionic Liquids Driven by Carbon Dioxide

Abstract: Ionic liquids (ILs) with a reversible hydrophobic-hydrophilic transition were developed, and they exhibited unique phase behavior with H2O: monophase in the presence of CO2, but biphase upon removal of CO2 at room temperature and atmospheric pressure. Thus, coupling of reaction, separation, and recovery steps in sustainable chemical processes could be realized by a reversible liquid-liquid phase transition of such IL-H2O mixtures. Spectroscopic investigations and DFT calculations showed that the mechanism behi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
57
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 42 publications
2
57
0
Order By: Relevance
“…As anew class of greener catalysts and solvents, ionic liquids (ILs) have received much attention from the scientific community,a nd the number of publications in this area has grown exponentially. [35][36][37][38][39][40][41] These liquid materials have been widely used in organic synthesis,c atalytic reactions, separation, material preparation, and biomass dissolution and conversion [41][42][43] owing to their unique features, such as high thermala nd chemicals tability, negligible vapor pressure, excellent solubility,a nd tunable structures andp roperties. [41,45,46] In recent years,I Ls have been applied as solvents and/or catalyst for CO 2 conversion,a nd significant achievements have been made in this field.…”
Section: Introductionmentioning
confidence: 99%
“…As anew class of greener catalysts and solvents, ionic liquids (ILs) have received much attention from the scientific community,a nd the number of publications in this area has grown exponentially. [35][36][37][38][39][40][41] These liquid materials have been widely used in organic synthesis,c atalytic reactions, separation, material preparation, and biomass dissolution and conversion [41][42][43] owing to their unique features, such as high thermala nd chemicals tability, negligible vapor pressure, excellent solubility,a nd tunable structures andp roperties. [41,45,46] In recent years,I Ls have been applied as solvents and/or catalyst for CO 2 conversion,a nd significant achievements have been made in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to realize product separation from IL-based solvents by means of pressure, [12] temperature, [13] and CO 2 . [14] For example, Leitner et al [12a] and Cheng et al [12b] found that a pressure-controlled supercritical CO 2 /IL system provides superior advantages in product separation, catalyst recycling, and reuse of the reaction media over traditional organic solvents. Davis et al [13a] and Wang et al [13b] reported thermodriven liquid-solid separation by using an alkane sulfonic acid IL as the solvent for esterification.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Physical and/or chemical CO 2 absorption by using ionic liquids has also received considerable interest due the chemicalv ersatility and favourable physical properties of ionic liquids. [14][15][16][17][18][19][20][21] Ap romising alternative is then to use ionic liquids impregnated in the pores of as olid porous support, for example, metal-organic frameworks and zeolites. [22][23][24][25][26][27][28][29] Recently,C lyburne and co-workersp roposed an ovel CO 2 sequestration procedureb ased on the cyanidea nion, which generatedthe cyanoformatea nion,N CCO 2 À ,f rom the exposure of ac oncentrated solution of [Ph 4 ][CN] in CH 3 CN to an atmosphere of CO 2 .…”
Section: Introductionmentioning
confidence: 99%